53. MEAN NUMBER OF ANALYZED EMBRYOS IN PGT-M CYCLES TO UNDERGO AT LEAST ONE EMBRYO TRANSFER. (August 2019) - Albanese, C.; Magli, M.C.; Crippa, A.; Benincasa, M.; Ferraretti, A.P.; Tabanelli, C.; Gianaroli, L.
Abstract : Introduction: Preimplantation genetic testing for monogenic diseases (PGT-M) is a clinical method developed to prevent the transmission of monogenic inherited disorders to the future offspring. The reproductive risk of carriers of single gene disorders depends on the typology of the disorder, with the probability of affected conceptions ranging from 25% in recessive or X-linked diseases to 50% in dominant diseases. Therefore, the possibility of having embryos suitable for transfer and the consequent chances of ongoing pregnancy are strictly related to the number of embryos available for the genetic analysis. The aim of this study was to evaluate how many embryos need to be analyzed for having one or more genetically transferrable embryos. Material and Methods: 86 carriers of genetic disorders performed 99 cycles of genetic analysis between January 2010 and September 2018. They were divided into two groups according to the typology of the disorder transmission. Group 1 included recessive and X-linked diseases (58 patients, 70 cycles of analysis), while with dominant disorders were in Group 2 (28 patients, 29 cycles of analysis). Maternal age was comparable in the two groups. Following blastocyst biopsy, embryos were vitrified to complete the genetic analysis. Results: Clinical results were the following. For both groups, the mean number of analyzed embryos to have genetically transferrable embryos are reported in the following table: Conclusions: Based on the reported data, we define for each case the minimum number of analyzable embryos needed to have one or more transferrable embryo depending on the typology of genetic disorder. Therefore, we eventually advise patients to undergo further oocyte retrievals for the best clinical outcome.